Correlations between Degree of Petal Fusion, Leaf Size and Fruit Size: A Case in Syzygium (Myrtaceae) (Biodiversitas Journal of Biological Diversity, 2009)
Syzygium is one of large genera of the flowering plants. In order to simplify the identification, a classification is required, e.g. based on degree of petal fusion, leaf size and fruit size. Due to variations of vegetative and generative characters, a correlation analysis was carried out. The aim of this research is to know the correlation between degree of petal fusion, leaf length and fruit diameter. The result of this research showed that there is positive correlation between those three variables. The increase of leaf size will increase fruit size and petal lobe depth.Key words: Syzygium, petal fusion, free, intermediate, fused petal, leaf, fruit size.